Strategi Ulama Dayah dalam Penangkalan Radikalisme pada Kalangan Santri - Paisal, Jon; Hasnadi, Hasnadi; Anwar, Anwar (Institut Agama Islam Negeri Padangsidimpuan, 2021)
The act of radicalism resulted in cases of terrorism in the name of religion so that it had an impact on social life in society. The role of the ulama is very important to anticipate that radical ideas and terrorism do not develop in society. This study aims to find out the strategy of the dayah ulama in countering radicalism among students in Aceh Jaya district through a qualitative descriptive approach. Data collection techniques through observation, interviews, and documentation. The results of this study indicate that the strategy to counter radicalism carried out by the dayah ulama is to convey da'wah which includes material on national insight delivered to students, da'wah about love for the homeland, cooperating with the TNI and Polri, habituation of exemplary attitudes, religious studies through recitations, activities of memorizing the Qur'an and recitation of books and carrying out religious activities in the dayah. The results of this study can be used as knowledge, information and comparisons for other institutions as an alternative step in the context of eradicating radicalism in Indonesia